Printed leaky‐wave antenna with stable gain and reduced cross polarization. Issue 12 (18th August 2022) - Kumar, Birendra; Ghosh, Jayanta
Abstract: A printed leaky‐wave antenna with stable gain and reduced cross‐polarization level is presented in this letter. The proposed antenna has the property of continuous backward‐to‐forward beam scanning with symmetrical scanning. The proposed antenna's unit cell consists of two unequal inclined stubs connected to a microstrip line. The angle between the stubs and their dimensions is designed optimally to obtain improved antenna performance. The antenna provides stable gain with peak gain 14.4 dBi and gain variation 2.55 dBi in the operating band 9.5–15 GHz. The maximum value of cross‐polarization level along the main beam is −30 dB. The design gives a scanning angle of 73° from −36° to +37° through broadside. Another important feature of the proposed antenna is that there is no gain reduction at the broadside radiation.